2013
DOI: 10.1177/0148607113504219
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Nutrition in Patients With Hemodynamic Failure Following Cardiac Surgery

Abstract: Our findings indicate that early EN is feasible in this type of patients and not associated with serious complications. However, it is difficult to attain an appropriate energy target by EN alone. These observations point to a need for monitoring of daily energy delivery and balance, as well as careful monitoring of warning signs of intestinal ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 45 publications
2
23
0
5
Order By: Relevance
“…Two independent prospective studies in cardiac surgery patients with hemodynamic failure reach to the same conclusion (Berger et al 2005;Flordelís Lasierra et al 2013). A study that included 70 patients with hemodynamic failure admitted to the ICU after cardiac surgery, 18 requiring mechanic support with intra-aortic balloon pump (IABP), revealed that EN is possible during the first postoperative week and as early as 24 h postsurgery.…”
Section: Role Of Early Enteral Nutrition In Cardiac Surgery Patients mentioning
confidence: 93%
“…Two independent prospective studies in cardiac surgery patients with hemodynamic failure reach to the same conclusion (Berger et al 2005;Flordelís Lasierra et al 2013). A study that included 70 patients with hemodynamic failure admitted to the ICU after cardiac surgery, 18 requiring mechanic support with intra-aortic balloon pump (IABP), revealed that EN is possible during the first postoperative week and as early as 24 h postsurgery.…”
Section: Role Of Early Enteral Nutrition In Cardiac Surgery Patients mentioning
confidence: 93%
“…En condiciones normales de ayuno el 20 % -25 % del gasto cardiaco, incrementando hasta al doble después de una comida, se observa en la circulación esplácnica consumiendo un 30 % del consumo corporal de O 2 , demostrando que en esta región la demanda metabólica es sumamente alta, donde el flujo sanguíneo puede aumentar más de 40 % durante la alimentación (3,19) .…”
Section: Nutrición Enteral Durante La Inestabilidad Hemodinámicaunclassified
“…El inicio de NET en un paciente con inestabilidad hemodinámica requerirá un aumento en la necesidad de O 2 intestinal causando vasodilatación local e incrementando el gasto cardiaco, lo cual podría generar isquemia a causa de la incapacidad para entregar O 2 e incrementar el gasto cardiaco, o contrarrestar el defecto de circulación al mismo nivel (19,20) . O puede, por el contrario, "robar" oxigenación a los órganos vitales (6) .…”
Section: Nutrición Enteral Durante La Inestabilidad Hemodinámicaunclassified
See 1 more Smart Citation
“…Enteral nutrition was started in 36 of 37 severely hemodynamically compromised patients, with complications noted in 62% (46% of those were constipation), though no complications were related to mesenteric ischemia. The authors concluded that in the hemodynamically compromised cardiac surgery patient, enteral nutrition is safe, though only 40% of the patients were able to reach their nutrition goals 30 . In a separate group of cardiac failure patients, Berger and colleagues showed intestinal absorption to be maintained, though decreased transit was present.…”
Section: Vasopressor Support and Enteral Nutrition: Clinical Evidencementioning
confidence: 99%